2023
DOI: 10.1021/acs.biochem.2c00666
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of a Highly Active Designed Phosphotriesterase for the Detoxification of Organophosphate Nerve Agents Reveals an Unpredicted Conformation of the Active Site Loop

Abstract: Neurotoxic organophosphorus compounds (OPs) pose a severe threat if misused in military conflicts or by terrorists. Administration of a hydrolytic enzyme that can decompose the circulating nerve agent into non-toxic metabolites in vivo offers a potential treatment. A promising candidate is the homo-dimeric phosphotriesterase originating from the bacterium Brevundimonas diminuta (BdPTE), which has been subject to several rational and combinatorial protein design studies. A series of engineered versions with muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(145 reference statements)
2
3
0
Order By: Relevance
“…Notably, in both structures the phosphonyl O atoms were observed to be at distances of 4.7 and 5.0 A ˚, respectively, from the buried �-Zn 2+ ion. The experimentally determined 3D structures of the OP acid products observed in the present study are consistent with the reported 3D structures of the complexes of PTEs with two other acid products: O,O-diethylphosphoric acid (DEP; PDB entry 3cak; Table 1; Kim et al, 2008) and ethyl-4-methylbenzylphosphonate (mEBP; PDB entry 7p85; Table 1; Job et al, 2023). The P-O O atoms of PTE-DEP and PTE-mEBP are placed symmetrically at 2.0-2.2 A ˚away from the two Zn 2+ ions, whereas in the case of the complex of the triester substrate analogue (C 2 H 5 O) 2 P(O)CH 2 phenyl-pCH 3 the P O O atom is 3.5 and 4.7 A ˚from the exposed �-Zn 2+ and the buried �-Zn 2+ , respectively (Vanhooke et al, 1996).…”
Section: Co-crystallization and Soaking Of Ops Into Ptessupporting
confidence: 90%
See 2 more Smart Citations
“…Notably, in both structures the phosphonyl O atoms were observed to be at distances of 4.7 and 5.0 A ˚, respectively, from the buried �-Zn 2+ ion. The experimentally determined 3D structures of the OP acid products observed in the present study are consistent with the reported 3D structures of the complexes of PTEs with two other acid products: O,O-diethylphosphoric acid (DEP; PDB entry 3cak; Table 1; Kim et al, 2008) and ethyl-4-methylbenzylphosphonate (mEBP; PDB entry 7p85; Table 1; Job et al, 2023). The P-O O atoms of PTE-DEP and PTE-mEBP are placed symmetrically at 2.0-2.2 A ˚away from the two Zn 2+ ions, whereas in the case of the complex of the triester substrate analogue (C 2 H 5 O) 2 P(O)CH 2 phenyl-pCH 3 the P O O atom is 3.5 and 4.7 A ˚from the exposed �-Zn 2+ and the buried �-Zn 2+ , respectively (Vanhooke et al, 1996).…”
Section: Co-crystallization and Soaking Of Ops Into Ptessupporting
confidence: 90%
“…11). Together with the similar short distances (2.0-2.2 A ˚) reported for PTE complexes with acidic OP products such as O,O-diethylphosphoric acid (Kim et al, 2008) and O-ethyl-4-benzylphosphonic acid (Job et al, 2023), it is suggested that, regardless of the size of the substituent, the enzyme is sufficiently flexible to utilize the stabilization machinery offered by the two Zn 2+ ions. Accordingly, the buried and exposed Zn 2+ ions are proposed to stabilize the developing high-energy charged TS, thereby lowering its energy content, with concomitant acceleration of the reaction relative to water alone.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…PLL and PTE share a (β/α) 8 fold with highly mobile loops that contribute to broadening their promiscuity to other substrates such as aryl-esters . Bacterial PTEs, although naturally efficient for the degradation of OP insecticides, have been further engineered in vitro for the development of biocatalysts close to catalytic perfection for decontaminating insecticides or chemical warfare agents. These variants may find application in bioremediation of agricultural contaminations or for prophylaxis protection against OP poisoning. , However, most PTEs have been isolated from mesophilic microorganisms and show moderate stability limiting their potential for bioremediation or development of medical countermeasures to face OP poisoning. , A subfamily of PLL, namely, PLL-A, is composed of enzymes isolated from thermostable and hyperthermostable bacteria or archaea. Special attention has thus been paid to PLL-A for developing high-potential biocatalysts as robust enzymes that may offer numerous biotechnological advantages including resistance to high temperatures, tolerance to solvents and denaturants, and long-term storage .…”
Section: Introductionmentioning
confidence: 99%
“… 15 Bacterial PTEs, although naturally efficient for the degradation of OP insecticides, have been further engineered in vitro for the development of biocatalysts close to catalytic perfection for decontaminating insecticides or chemical warfare agents. 16 23 These variants may find application in bioremediation of agricultural contaminations or for prophylaxis protection against OP poisoning. 24 , 25 However, most PTEs have been isolated from mesophilic microorganisms and show moderate stability limiting their potential for bioremediation or development of medical countermeasures to face OP poisoning.…”
Section: Introductionmentioning
confidence: 99%